Comprehensive examination of haematological parameters of patients operated due to testicular torsion. (5th June 2020) - Merder, Erkan; Bozkurt, Muammer; Ariman, Ahmet; Sezgin, Mehmet Ali; Culha, Mehmet Gokhan; Altunrende, Fatih
Abstract: We aimed to investigate the pre‐operative predictive role of haematological parameters in patients with testicular torsion. The medical records of patients operated between January 2016 and November 2018 were retrospectively analysed. The demographic characteristics and complete blood count of the patients were recorded. We divided the patients who operated with testicular torsion into two groups: detorsion (Group 1) and orchiectomy (Group 2). A control group (Group 3) was created from healthy volunteers. All haematological parameters and other demographic data were compared between three groups. A total of 144 participants were included; Group 1, Group 2 and Group 3; 61, 27 and 56 respectively. The duration of symptoms and monocyte counts were found statistically significantly higher in patients undergoing orchiectomy than detorsion ( p  < .01). We found a significant difference in terms of neutrophil, lymphocyte, monocyte counts and neutrophil–lymphocyte ratio between patients with testicular torsion and controls. We also found that the monocytes count and symptom duration differed significantly between the detorsion group and the orchiectomy group. It is obvious that there is contradictory information according to the studies in the literature. We can say that the duration of symptoms and the number of monocytes are predictors of testicular viability.